2023
DOI: 10.1186/s12966-023-01499-x
|View full text |Cite
|
Sign up to set email alerts
|

The status of active after-school clubs among primary school children in England (UK) after the COVD-19 lockdowns: implications for policy and practice

Robert Walker,
Ruth Salway,
Danielle House
et al.

Abstract: Background Children’s physical activity in England is more dependent on active clubs after the COVID-19 pandemic. However, it is unclear how the COVID-19 pandemic and related cost-of-living crisis have impacted on active club participation, costs and provision. This mixed-methods natural experiment explored school-based and community-based active clubs after lockdowns, using a unique combination of data sources to highlight implications for policy and practice post-COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…To encourage children to be active, schools need a range of clubs and staff capacity to support varying child needs, 51,52 however, other Active-6 analysis has found an increased demand for school-based active clubs since the lockdowns, which schools are struggling provide. 61 Other recent evidence, including Active-6, has also found that the impact of the pandemic on child physical activity, and the recovery, is uneven across demographic groups such as gender, age, ethnicity and SES. 25,62 These findings are mirrored in this study, which suggest that children who were active before the pandemic lockdowns returned to active clubs, and those who were less active are now even harder to engage, resulting in a greater polarisation of child ability and activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…To encourage children to be active, schools need a range of clubs and staff capacity to support varying child needs, 51,52 however, other Active-6 analysis has found an increased demand for school-based active clubs since the lockdowns, which schools are struggling provide. 61 Other recent evidence, including Active-6, has also found that the impact of the pandemic on child physical activity, and the recovery, is uneven across demographic groups such as gender, age, ethnicity and SES. 25,62 These findings are mirrored in this study, which suggest that children who were active before the pandemic lockdowns returned to active clubs, and those who were less active are now even harder to engage, resulting in a greater polarisation of child ability and activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to patterns seen in children, where organised active clubs have become the mainstay of activity for children following lockdowns, 47 particularly active clubs based at the child's school, but this has been socio-demographically patterned. 46,47,62,63 The qualitative discussions highlighted the importance of social connection during the pandemic for increasing enjoyment and effort in physical activity. Connecting with others was often one of the main reasons for engaging in online physical activity and going for walks with friends.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large number of children do not meet the World Health Organization (WHO) recommended average of 60 minutes of moderate-to-vigorous physical activity (MVPA) per day (1,2), with recent accelerometer data suggesting that only 41% of 10-11 year old children meet the recommendation (3,4). As we emerge from the COVID-19 pandemic, the way in which children are physically active has changed, with fewer children engaging in unstructured forms of physical activity, such as active play, and an increased dependence on structured activities, such as active school clubs (5)(6)(7). As girls and children from lower socio-economic groups have greater challenges in engaging in structured activities, these groups may be at risk of lower than their pre-pandemic levels of physical activity (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…As we emerge from the COVID-19 pandemic, the way in which children are physically active has changed, with fewer children engaging in unstructured forms of physical activity, such as active play, and an increased dependence on structured activities, such as active school clubs (5)(6)(7). As girls and children from lower socio-economic groups have greater challenges in engaging in structured activities, these groups may be at risk of lower than their pre-pandemic levels of physical activity (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%